Grammatical and Mechanical Errors Analysis in Writing Recount Text - Kardelius Giawa; Sahlan Tampubolon; Kammer Tuahman Sipayung (Journal of Language Education (JoLE), 2024)
In writing skills, learners would be able to put their feelings, ideas, arguments, willingness, and their minds into words, sentences, and even stories. The aims of this study are to identify the students’ grammatical, and mechanical errors, and dominant errors and to figure out the factors that caused the grammatical and mechanical errors made by first-grade students of SMK Negeri 1 Amandraya in writing recount text. The method of this research is qualitative descriptive text. The subject of research is first grade accounting of SMK Negeri 1 Amandraya and object was grammatical and mechanical errors. The samples in this study was be first-class accounting 24 students who are learning English subject at SMK Negeri 1 Amandraya. The result of this research based on grammatical errors was 141 errors, based on the mechanical error were 9 errors, the dominant error in writing recount text were misinformation 48%. Some factors that lead to the error because of limited of vocabulary, lack interest of learning English subject, and not mastering tenses, using of punctuation.